Nieodparta sila - Steel, Danielle; Mazan, Maciejka (Warszawa : Amber, 2000)
Polish translation of "Irresistible Forces". Steve, a gifted physician and Meredith, an investment banker suffer urban trauma, a childless marriage and the irresistible forces which tear apart lives and hearts.
Keywords: Commuter marriage -- Fiction; Investment bankers -- Fiction; Physicians -- Fiction; San Francisco (Calif.) -- Fiction; New York (N.Y.) -- Fiction